THE RELATION OF WORK MOTIVATION, WORK DISCIPLINE ON TEACHER PERFORMANCE THROUGH TEACHER PROFESSIONAL ATTITUTE - Shaleh, Anshari; Suhaimi; Ngadimun (Journal of K6, Education and Management, 2019)
Teacher performance is an activity in learning which is expected to be able to improve the quality and relevance of education. In the implementation of school, performance is influenced by many factors and interrelated for example work motivation, work discipline, and teacher professional attitude. This research aims to analyze the relationship between work motivation, teachers' professional attitude, discipline, and performance. Data were obtained from 173 elementary school teachers at the district of South Labuan Amas, through questionnaires and analyzed using the path analysis. The result of this research shows that there is a strong relationship between work motivation with teacher professional attitude, performance, and discipline. There is a strong relationship between work motivation with the teacher's performance, discipline, and professional attitude. Furthermore, there is a weak relation between work discipline and the teacher's professional attitude, discipline, and attitude. Advice this research to increase the factors that affect the teacher performance, the school should reward teachers for performance.